Professional Medical Writer Assistance in Oncology Clinical Trials. (17th September 2020) - Kouzy, Ramez; Abi Jaoude, Joseph; Mainwaring, Walker; Lin, Timothy A.; Miller, Austin B.; Jethanandani, Amit; Espinoza, Andres F.; Verma, Vivek; Fuller, Clifton D.; Minsky, Bruce D.; Rödel, Claus; Taniguchi, Cullen M.; et al.
Abstract: Background: The use of professional medical writers (PMWs) has been historically low, but contemporary data regarding PMW usage are scarce. In this study, we sought to quantify PMW use in oncologic phase III randomized controlled trials (RCTs). Methods: We performed a database query through ClinicalTrials.gov to identify cancer‐specific phase III RCTs; we then identified whether a PMW was involved in writing the associated trial manuscript reporting primary endpoint results. Results: Two‐hundred sixty trials of 600 (43.3%) used a PMW. Industry‐funded trials used PMWs more often than nonindustry trials (54.9% vs. 3.0%, p < .001). Increased PMW usage was further noted among trials meeting their primary endpoint (53.4% vs. 32.9%, p < .001) and trials that led to subsequent Food and Drug Administration approval (63.1% vs. 36.3%, p < .001). By treatment interventions, PMW use was highest among systemic therapy trials (50.2%). Lastly, the use of PMWs increased significantly over time (odds ratio: 1.11/year, p = .001). Conclusion: PMW use rates are high among industry‐funded trials. We urge continued and increased transparency in reporting the funding and use of PMWs. Abstract : Considering the increase in industry‐sponsored cancer clinical trials, the use of professional medical writers for publication of trial results has become an increasingly important topic. This brief communication reports the current rate of involvement of medical writers in publications of cancer clinical trials.